Productivity dynamics of agroecosystems under prevailing and alternative management practices across the United States - Omodara E. Obisesan; Adam P. Schreiner-McGraw; Jeffrey D. Wood; Jiquan Chen; Joshua D. Gamble; Timothy J. Griffis; Christina M. Helseth; Makki Khorchani; Claire L. Phillips; Kathryne Rumora; Russell L. Scott; Xiangmin Sun; et al. (Agricultural and Forest Meteorology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

Capturing free-roaming dogs for sterilisation: A multi-site study in Goa, India - H.R. Fielding; K.A. Fernandes; V.R. Amulya; D. Belgayer; A. Misquita; R. Kenny; A.D. Gibson; L. Gamble; B.M.de C. Bronsvoort; R.J. Mellanby; S. Mazeri (Preventive Veterinary Medicine, 2023)

The compositional diversity and temporal evolution of an active andesitic arc stratovolcano: Tongariro, Taupō Volcanic Zone, New Zealand - Leo R. Pure; Colin J. N. Wilson; Bruce L. A. Charlier; John A. Gamble; Dougal B. Townsend; Graham S. Leonard (Contributions to Mineralogy and Petrology, 2023)
New geochemical data, including Sr–Nd–Pb isotopes for whole-rock and groundmass samples, are reported for edifice-forming eruptives at Tongariro volcano, New Zealand, which span its ~ 350 ka to late Holocene history. Tongariro eruptives are medium-K basaltic-andesites to dacites (53.0–66.2 wt% SiO 2 ) that evolved via assimilation-fractional crystallisation (AFC) processes partly or mostly in the uppermost 15 km of the crust. When ordered chronologically using a high-resolution 40 Ar/ 39 Ar-dated eruptive stratigraphy, the compositional data show systematic 10–130 kyr cycles. Mafic replenishment events inferred from MgO values occurred at ~ 230, ~ 151, ~ 88 and ~ 56 ka and in the late Holocene, with high-MgO flank vents erupting at ~ 160, ~ 117, ~ 35 and ~ 17.5 ka. Cycles in Sm/Nd, 87 Sr/ 86 Sr, 143 Nd/ 144 Nd and Pb isotopic ratios, which are decoupled from MgO, K 2 O and Rb/Sr cycles, indicate periods of prolonged crustal residence of magmas from ~ 230 to ~ 100 ka and ~ 95 to ~ 30 ka. AFC modelling shows that intermediate and silicic melt compositions, with r-values between 0.1 and 1, are needed to reproduce Tongariro compositional arrays. AFC models also indicate that ~ 20% of the average Tongariro magma comprises assimilated (meta)sedimentary basement material. Locally, Tongariro and adjacent Ruapehu volcanoes attain their most crust-like 87 Sr/ 86 Sr and 143 Nd/ 144 Nd compositions at ~ 100 and ~ 30 ka, paralleling with zircon model-age crystallisation modes at the rhyolitic Taupō volcano ~ 50 km to the NNE. These coincidences suggest that the timing and tempo of magma assembly processes at all three volcanoes were contemporaneous and may have been tectonically influenced since at least 200 ka.

Modelling bodyweight to avoid anthelmintic underdosing of goats in resources-limited settings - M. J. Evans; C. L. Kaona; A. K. Barros; J. L. Burdon Bailey; P. Chikungwa; L. M. Costa-Junior; L. Gamble; A. M. Hopker; R. F. Kelly; F. Lohr; R. Silva; N. D. Sargison (Tropical Animal Health and Production, 2023)
Improved management of livestock in resource-limited settings can provide a means towards improved human nutrition and livelihoods. However, gastrointestinal nematodes (GIN) are a significant production-limiting factor. Anthelmintics play a role in GIN management; however, few anthelmintic classes are available in many low-middle-income countries. Utilising a limited range of classes may increase selection for anthelmintic resistance; therefore, strategies to reduce other selective pressures are of heightened importance. Avoiding anthelmintic underdosing is one such strategy, but it can be challenging without access to accurate bodyweight measurement. Many previous studies have used thoracic girth as a practical proxy for bodyweight in goats; however, they have rarely considered the potential impact of natural variation on therapeutic doses. Here, the relationship between bodyweight and thoracic girth was modelled using data from 820 goats from three Malawian biomes in two seasons, with the specific aim of avoiding underestimation of bodyweight. The internally cross-validated linear regression (∛Weight ~ 0.053 + 0.040*Girth, R 2 = 0.92, rounded up to the nearest 5 kg) was validated against data from an additional 352 Malawian goats (1.4% of goats allocated an underdose and 10.2% allocated a dose > 200% of bodyweight). The equation was further externally validated using an historical dataset of 150 goats from Assam, India (2.7% of goats were allocated to an underdose and 24.8% allocated to a > 200% of bodyweight). These results suggest that a more globally generalisable approach may be feasible, provided the accuracy of the estimate is considered alongside the therapeutic index of the pharmaceutical.

A pilot study of a culturally-appropriate, educational intervention to increase participation in cancer clinical trials among African Americans and Latinos - Jennifer Cunningham-Erves; Tilicia L. Mayo-Gamble; Pamela C. Hull; Tao Lu; Claudia Barajas; Caree R. McAfee; Maureen Sanderson; Juan R. Canedo; Katina Beard; Consuelo H. Wilkins (Cancer Causes & Control, 2021)

Improved in vivo targeting of BCL-2 phenotypic conversion through hollow gold nanoshell delivery - Erin Morgan; John T. Gamble; Martin C. Pearce; Daniel J. Elson; Robert L. Tanguay; Siva Kumar Kolluri; Norbert O. Reich (Apoptosis, 2019)

Biophysical interactions in perennial biomass alley cropping systems - Joshua D. Gamble; Gregg Johnson; Dean A. Current; Donald L. Wyse; Diomides Zamora; Craig C. Sheaffer (Agroforestry Systems, 2019)

Phosphate Removal from Agricultural Drainage Water Using an Iron Oxyhydroxide Filter Material - Barry J. Allred; Luis R. Martinez; Debra L. Gamble (Water, Air, & Soil Pollution, 2017)

In-Package Inactivation of Pathogenic and Spoilage Bacteria Associated with Poultry Using Dielectric Barrier Discharge-Cold Plasma Treatments - Michael J. Rothrock; Hong Zhuang; Kurt C. Lawrence; Brian C. Bowker; Gary R. Gamble; Kelli L. Hiett (Current Microbiology, 2017)

Harvest Date Effects on Biomass Yield, Moisture Content, Mineral Concentration, and Mineral Export in Switchgrass and Native Polycultures Managed for Bioenergy - Joshua D. Gamble; Jacob M. Jungers; Donald L. Wyse; Gregg A. Johnson; John A. Lamb; Craig C. Sheaffer (BioEnergy Research, 2015)

Establishment and early productivity of perennial biomass alley cropping systems in Minnesota, USA - Joshua D. Gamble; Gregg Johnson; Craig C. Sheaffer; Dean A. Current; Donald L. Wyse (Agroforestry Systems, 2014)

Hydroperiods of created and natural vernal pools in central Ohio: A comparison of depth and duration of inundation - Debra L. Gamble; William J. Mitsch (Wetlands Ecology and Management, 2009)

Limitations of regulated “buffer zones” for the conservation of marbled salamanders - Lloyd R. Gamble; Kevin McGarigal; Christopher L. Jenkins; Brad C. Timm (Wetlands, 2006)

Environmental Contaminants in Blood, Hair, and Tissues of Ocelots from the Lower Rio Grande Valley, Texas, 1986–1997 - Migual A. Mora; Linda L. Laack; M. Clare Lee; Jose Sericano; Robert Presley; Piero R. Gardinali; Lawrence R. Gamble; Stephen Robertson; Donell Frank (Environmental Monitoring and Assessment, 2000)

Trichinella spiralis infection in voles alters female odor preference but not partner preference - Sabra L. Klein; H. Ray Gamble; Randy J. Nelson (Behavioral Ecology and Sociobiology, 1999)